Hemodialysis duration and underweight as a risk factors of renal osteodystrophy (chronic kidney disease - mineral bone disorder) on regular hemodialysis patient - Andika, Gde Dedy; Kawiyana, I. Ketut Siki; Wiratnaya, I. Gede Eka; Kandarini, Yenny (International Journal of Research in Medical Sciences, 2021)
Background: Chronic kidney disease (CKD) is related to systemic disorders affecting multiple organs, including the bone, known as osteoporosis or renal osteodystrophy. Long duration of hemodialysis and underweight based on the Body Mass Index (BMI) is thought to be risk factors for renal osteodystrophy. This study aims to determine the risk factors in the form of hemodialysis duration and underweight in the incidence of renal osteodystrophy in patients with CKD stage 5. Methods: This research is an analytic observational study with case and control group involving 26 patients. In each group, anamnesis, anthropometric examination and bone mass density (BMD) examination with DEXA were performed. Analysis using Chi-squared test, and an odds ratio (OR) calculation were performed to determine the effect of hemodialysis duration and underweight as risk factors for renal osteodystrophy in CKD patients Results: There is a significant difference in the duration of hemodialysis (p=0.047, 95% CI=0.97-29.39) and underweight (p=0.011, 95% CI=1.39-141.49) between the CKD patient group. In addition, it was also found that the duration of HD (OR=5.33) and underweight (OR=14) were significant risk factors for renal osteodystrophy in CKD patients. Conclusions: There is significant differences in the duration of hemodialysis and underweight between CKD patients with renal osteodystrophy and without renal osteodystrophy. Hemodialysis duration and underweight are also a significant risk factors for renal osteodystrophy in patients with CKD.